MARKET TESTING OF FOOTWEAR STAKEHOLDER CHAIN MARKETPLACE - David Sukardi Kodrat; Tina Melinda; Denpharanto Agung Krisprimandoyo (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
Footwear Stakeholder Chain Marketplace (FSCM) is a marketplace that integrates suppliers, producers, consumers, logistics services and funding institutions. Industry groups with core industries that interact intensively and form partnerships, both with supporting industries and with related industries can be said to be clusters in the marketplace. The purpose of this study is to examine the horizontal and vertical linkages in FSCM including: suppliers, manufacturers, makers, buyers, carriers, stores, sellers, distributors, retailers and customers. Testing is carried out using the market testing method using in-person usability testing techniques to improve performance and user experience. The procedure is done to collect respondents, find a comfortable room, and record the whole process. The results show that the home, consumers, suppliers, manufacturers, and forums display create a unique user experience. When consumers buy certain products, words that reinforce consumer choices will appear, such as: Good choice!” or “Yum! We love that one". In addition, consumers also have the opportunity to display their designs and at the same time sell them in the artist shop. Suppliers and producers have the opportunity to share access.